New housing association development and its potential to reduce concentrations of deprivation: An English case study. (December 2016) - Crook, Tony; Bibby, Peter; Ferrari, Ed; Monk, Sarah; Tang, Connie; Whitehead, Christine
Social housing across Western Europe has become significantly more residualised as governments concentrate on helping vulnerable households. Many countries are trying to reduce the concentrations of deprivation by building for a wider range of households and tenures. In England this policy has two main strands: (1) including other tenures when regenerating areas originally built as mono-tenure social housing estates and (2) introducing social rented and low-cost homeownership into new private market developments through planning obligations. By examining where new social housing and low-cost home ownership homes have been built and who moves into them, this paper examines whether these policies achieve social mix and reduce spatial concentrations of deprivation. The evidence suggests that new housing association development has enabled some vulnerable households to live in areas which are not deprived, while some better-off households have moved into more deprived areas. But these trends have not been sufficient to stem increases in deprivation in the most deprived areas.